Internationalisation Strategies of Chinese Automakers: Cases Studies of Geely Auto and Chang'an Auto - Pan, Youbei (2013)
Internationlisation theories are always studied on Western Multinational Enterprises. Therefore, internationalisation process theory may not be able to fully explain Chinese automobile firms’ internationalisation processes. In the case of China, internationlisation strategies are not very rational and clear. Instead, there are always institutional and unplanned parts involved in. This dissertation tends to examine this point based on two cases: Geely Auto and Chang’an Auto.